Prevalence of mycotoxigenic fungi and ochratoxin A in coffee (Coffea arabica L.) - Legese Hagos; Meseret Guta; Ketema Bacha (Cogent Food & Agriculture)
Coffee is one of the most important agricultural export commodities being relied upon to generate revenue of foreign currency. To this end, it has to be of high quality to satisfy expectation and standards of international coffee markets. However, several mycoflora are naturally associated with coffee, some of which may produce fungal toxins such as Ochratoxin A (OTA) unless the safety of the products is carefully managed. Therefore, this research was initiated to identify the prevalent mycotoxigenic fungi and evaluate the presence of OTA in coffee beans collected from the soil surface and from wet and dry processing coffee mills. A total of 77 coffee samples were collected from Gera, Gomma, Limu Kosa and Mana districts of Jimma Zone, Oromia Regional State, Ethiopia. Malt Extract Agar (MEA) was used for the isolation and identification of fungi using macro and microscopic characteristics of the isolates, and High Performance Liquid Chromatography (HPLC) was used to detect and quantify OTA in green coffee beans using the AOAC method. Different fungal genera, including Aspergillus (84.74%), Fusarium (8.75%), Penicillium (5.49%), and Rhizopus (1.02%), were found associated with coffee beans collected from different coffee processes. Mean OTA values of 6.24 µg/kg, 2.05 µg/kg and 1.2 µg/kg were detected in coffee bean samples collected from soil surface, dry, and wet processed samples, respectively. In the present study, coffee beans collected from soil surfaces were more contaminated with various filamentous molds and their toxins than the dry and wet processed coffee beans with relatively better safety status.